Chiral Supramolecular Nanoarchitectures from Macroscopic Mechanical Rotations: Effects on Enantioselective Aggregation Behavior of Phthalocyanines. (31st October 2019) - Kuroha, Mizuki; Nambu, Shohei; Hattori, Shingo; Kitagawa, Yuichi; Niimura, Kazuhiro; Mizuno, Yuki; Hamba, Fujihiro; Ishii, Kazuyuki
Abstract: Fluid dynamics, resulting from the macroscopic mechanical rotation of either a rotary evaporator or a magnetic stirrer, has been shown to selectively induce one of two enantiomers (mirror‐image structures) in certain nanoscale supramolecules. As an alternative to giving a chiral twist to synthesized supramolecules or polymers, it is a challenge to reproducibly prepare chiral species by only using macroscopic mechanical rotations. Demonstrated here is a highly reproducible method for rotary‐evaporation‐induced enantioselective H‐aggregation of achiral phthalocyanines. Chiral induction mechanisms are proposed by using the chiroptical‐sign‐based absolute structures. These results will provide insight to the origin of the homochirality of life, and serves as a pioneering study in a novel scientific field in terms of admixing nanoscale molecular chemistry and macroscopic fluid dynamics. Abstract : Rotationsverdampfung induziert die enantioselektive Aggregation achiraler Phthalocyanine zu chiralen Überstrukturen. Die Mechanismen der chiralen Induktion werden postuliert und ebnen den Weg zur Generierung nanoskaliger molekularer Chiralität durch makroskopisches mechanisches Rotieren.